Genetically modified organisms and sustainable crop production: A critical review (Journal of the Bangladesh Agricultural University, 2013)
Fighting against global hunger in the adverse climatic condition is a major concern of the governments around the globe. The pace of population growth is overwhelmingly defeating the growth in crop production. In this context, introduction of GMO is emerging as a probable solution for sustainable crop production. However, such developments are not beyond criticism. This paper assesses and evaluates the prospects and challenges of introduction of GMO in a global perspective. Experiences of GM crop cultivation in different countries are also considered. This paper is a review of all accessible literature on GMO and sustainable crop production. This review will give a flavor of the on going debate and help take decision by the interested countries regarding GMO adoption. Furthermore, on the basis of the review this paper suggests some policy recommendations.DOI: http://dx.doi.org/10.3329/jbau.v10i2.14921 J. Bangladesh Agril. Univ. 10(2): 291-296, 2012